Think like a futurist : know what changes, what doesn't, and what's next - Sommers, Cecily, 1961- (San Francisco, CA : Jossey-Bass, 2012)
Sommers shows how to track changes, explore questions, and engage in new thinking that connects today's pressures with tomorrow's realities. By understanding intersecting potentials that one day may impact your organization, you can readily spot emerging trends and market shifts, uncovering opportunities on the horizon.
Know: the four forces of change -- New: the zone of discovery -- Do: the 5 percent rule -- What's next toolkit.
Includes bibliographical references (p. 239-243) and index.
Keywords: Business forecasting; Strategic planning; Diffusion of innovations; New products; Creative thinking; Organizational change